Исследование углеводородных систем для определения количественных характеристик в трубопроводах учебное пособие для вузов - Чухарева, Н. В. специалист в области нефтегазового дела доцент Томского политехнического университета, кандидат химических наук 1967- (Изд-во ТПУ, 2012)
This course book includes the following issues: physico-chemical and technological features of oil and gas connected with such problems as fluid and gas regimes, quality measurement and different hydrocarbon flow rates. Classification and control -measurement devices in calculating hydrocarbon quantity are described. Hydrocarbon flow measurement technology applied in oil and gas units are depicted. It is appropriate for students of the Geology & Petroleum Engineering Institute; specialty- 130501 "Design, construction and operation of oil pipelines and oil tank storage"